15th International Symposium on Cells of the Hepatic Sinusoid, 2010 - DeLeve, Laurie D. (Liver Int, 2011)
This is a meeting report of the presentations given at the 15th International Symposium on Cells of the Hepatic Sinusoid, held in 2010. The areas covered include the contributions of the various liver cell populations to liver disease, molecular and cellular targets involved in steatohepatitis, hepatic fibrosis and cancer and regenerative medicine. In addition to a review of the science presented at the meeting, this report provides references to recent literature on the topics covered at the meeting.